2016
DOI: 10.1098/rspb.2016.0608
|View full text |Cite
|
Sign up to set email alerts
|

Plant–soil feedbacks promote negative frequency dependence in the coexistence of two aridland grasses

Abstract: Understanding the mechanisms of species coexistence is key to predicting patterns of species diversity. Historically, the ecological paradigm has been that species coexist by partitioning resources: as a species increases in abundance, self-limitation kicks in, because species-specific resources decline. However, determining coexistence mechanisms has been a particular puzzle for sedentary organisms with high overlap in their resource requirements, such as plants. Recent evidence suggests that plant-associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 47 publications
(70 reference statements)
0
75
0
Order By: Relevance
“…Comparing density treatments in conditioned soil to the same treatments in sterilized soils captures the effect of all soil microbes, since the reference soil should contain virtually no microbes. This might be a suitable choice for studies that wish to isolate the impacts of soil microbes and compare the strength of microbial effects to other processes (Chung and Rudgers , which asked whether soil microbes promoted plant coexistence). One the other hand, unconditioned soils may harbor microbial propagules such as dormant spores (Lennon and Jones ) that could potentially affect the focal plant.…”
Section: Applying Modern Coexistence Theory To Plant–soil Microbe Intmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing density treatments in conditioned soil to the same treatments in sterilized soils captures the effect of all soil microbes, since the reference soil should contain virtually no microbes. This might be a suitable choice for studies that wish to isolate the impacts of soil microbes and compare the strength of microbial effects to other processes (Chung and Rudgers , which asked whether soil microbes promoted plant coexistence). One the other hand, unconditioned soils may harbor microbial propagules such as dormant spores (Lennon and Jones ) that could potentially affect the focal plant.…”
Section: Applying Modern Coexistence Theory To Plant–soil Microbe Intmentioning
confidence: 99%
“…, Bever ). Differences in the way competing plants interact with soil microbes might promote plant coexistence (Bever , Chung and Rudgers ). Alternatively, soil microbes could favor certain plants over their competitors, creating variation in species' relative abundance (Klironomos , Mangan et al.…”
Section: Introductionmentioning
confidence: 99%
“…3) suggested that increased interannual CV in climate under a changing mean may be an overlooked, but important driver of the Great Plains to Chihuahuan Desert grassland transition. Thus, greater temporal variance in climate under a changing mean climate may explain the grassland ecotone enigma, where the competitively inferior black grama (Peters andYao 2012, Chung andRudgers 2016) appears to be replacing its more competitive congener, blue grama (Collins and Xia 2015). 3B).…”
Section: New Explanations For Ongoing Ecosystem Transitions In Drylandsmentioning
confidence: 99%
“…, Pendergast et al. , Chung and Rudgers ). Furthermore, experiments are typically conducted in artificial environments, which are disconnected from the dynamics of species in natural landscapes (but see Burns and Brandt , Pellkofer et al.…”
Section: Introductionmentioning
confidence: 98%
“…). Such feedbacks could increase the magnitude of negative intraspecific interactions relative to interspecific interactions, potentially stabilizing species coexistence and slowing successional change (Burns and Brandt , Chung and Rudgers ). Alternatively, plant–soil feedbacks could promote directional change in plant community composition, if feedbacks favor the establishment of later‐successional species (Kardol et al.…”
Section: Introductionmentioning
confidence: 99%